Dr. Abdulrazaq Mohammed Al Butayhy and his Scientific Curriculum in Human Geography - Abdullah Jasim, Wisam (Al-Adab Journal, 2019)
Human geography is a link with other humanities, as these sciences give the spatial dimension that they lack, and the topics that are subject to geographical naming are numerous, but their detailed differences underline the fact that all the geographical scientists regardless of their specialties and interests are under 'an umbrella' of similar questions about different phenomena, whether natural or human.The aim of the study is to identify a distinguished Iraqi person, a scientist and thinker of Iraq; Prof. Dr. Abdulrazaq Mohammed Al Butayhy, one of the leading professors in modern and contemporary geography, in a very modest contribution to the right of one of Iraq's creators and scholars, and the importance of the study is in familiarizing the academic community with his scientific personality and his active contribution to the establishment of the rules of contemporary geography and, in particular, the methodology of scientific research in general.